TRIPLE BOTTOM LINE IN SUSTAINABLE HUMAN RESOURCE MANAGEMENT: A BIBLIOMETRIC ANALYSIS - Anindya Prastiwi Setiawati; Nugrahini Susantinah Wisnujati; Trisadini Prasastinah Usanti; Savitri Winawati Hidayat; Ristani Widya Inti (Acitya Wisesa: Journal of Multidisciplinary Research, 2025)
The integration of sustainability principles into human resource management has gained increasing scholarly attention, yet comprehensive frameworks addressing economic, social, and environmental dimensions simultaneously remain insufficiently developed. Whilst previous research has examined socially responsible HRM, green HRM, and sustainable work systems independently, the fragmented nature of these investigations limits understanding of how organisations can operationalise triple bottom line principles through strategic human resource management. This study employs a bibliometric analysis and systematic literature review to explore the incorporation of triple bottom line concepts into sustainable human resource management scholarship. Bibliometric data were collected from the Scopus database covering publications between 2015 and 2025, analysed using VOSviewer and Bibliometrix package in R to map intellectual structures, publication trends, and thematic evolution. The findings reveal substantial growth in sustainable HRM and green HRM research over the past decade, with three dominant typologies identified: socially responsible HRM, green HRM, and triple bottom line HRM. However, persistent challenges include conceptual fragmentation, inside-out economic orientations, and geographical imbalances in research contributions. The study contributes empirically by documenting intellectual evolution of triple bottom line research in sustainable HRM and conceptually by synthesising how economic viability, social equity, and environmental responsibility are progressively operationalised within human resource management domains.